Graphene-based photocatalysts for oxygen evolution from water. Issue 9 (22nd December 2014) - Pan, H.; Zhu, S.; Lou, X.; Mao, L.; Lin, J.; Tian, F.; Zhang, D.
Abstract : Recent achievements of GR-based photocatalysts for oxygen evolution from water are summarized with perspectives on major challenges and opportunities. Abstract : Graphene (GR) has triggered new research fields in material science, due to its unique monolayer structure, remarkably high conductivity, superior electron mobility, extremely high specific surface area and chemical stability. It is considered to be an ideal matrix and electron mediator of semiconductor nanoparticles for environmental and energy applications. In particular, GR-based nanocomposites have attracted significant attention when used as photocatalysts. This review will focus on oxygen evolution from water using GR-semiconductor photocatalytic systems. Recent achievements of effective strategies in the fabrication of GR-based semiconductor photocatalysts for oxygen evolution from water are summarized. Furthermore, the morphology control and composition design of semiconductors on GR sheets are also reviewed in relation to their photocatalytic oxygen generation properties. This review ends with a summary and some perspectives on the major challenges and opportunities in the future research.